Star trek the original series. Season 3 [videorecording (Blu-Ray)] : the complete series - Roddenberry, Gene; Courage, Alexander (CBS Studios ; Paramount, 2021)
The U.S.S. Enterprise embarks on more missions to explore the galaxy; she is commanded by Captain James T. Kirk. Along his side is his First Officer Mr. Spock, who is from the planet Vulcan. With a determined crew, the Enterprise encounters Klingons, Romulans, time paradoxes, Tribbles and many more problems. Their mission is to explore strange new worlds, to seek new life and new civilizations, to boldly go where no man has gone before.